METODOLOGI ANALISIS GENDER DALAM HUKUM ISLAM: Methodology of Gender Analysis in Islamic Law - Ramli, Mohd Anuar (Jurnal Syariah, 2013)
Gender analysis is social analysis method which has been applied in Islamic Jurisprudence studies. Islamic rulings can be either immutable or flexible which subject to the process of change. As for the gender discourse, the similar categories of rulings can also be applied. This article hence discusses the methodologies in gender analysis which are permissible in Islamic jurisprudence. For further clarification, the case of women testimonial right has been elaborated. It is found that although the testimony given by a woman is generally less valued than that of a man, there are number of cases which show that the testimony by former has a similar credential as the one which is given by the latter. Hence, the general view of the superiority of man to testify in some cases, does not imply the discriminatory attitude of Islam towards any type of gender. It is indeed only a manifestation that Islam has designated different roles to different gender